Coggle to boost collaborative learning: A prewriting strategy for writing Malaysia university english test - Mohammad Musab, Azmat Ali; Ahmad Mahfuz, Mohamed Anuar (Penerbit UMPSA, 2024)
Second language learners frequently need help generating a good piece of writing due to their failure to focus on the most critical stage of writing, the prewriting stage. Most students need to pay more attention to the importance of the prewriting stage, and starting writing is the most challenging part for most students. Many students assume that writing focuses on grammar per se rather than vocabulary and some other element for it to be perfect and readable. This study aims to investigate SMK Sultan Ahmad Form Six students' perceptions of using Coggle as their prewriting strategy. A questionnaire was used to collect both quantitative and qualitative data. Therefore, 30 Form Six students of Sekolah Menengah Kebangsaan Sultan Ahmad with different band achievements in MUET (Malaysian University English Test) were selected to participate in this study. The analysis of the data indicated that the majority of the students had positive perceptions of the use of Coggle in enhancing their writing skills. Coggle helps the students plan their writing, adopt a deeper understanding of the writing topics, and promote creativity. The study's findings are hoped to provide insights to the students, teachers, and curriculum designers on integrating Coggle in ESL (English as a Second Language) writing classes. Several pedagogical implications are highlighted. One of the major obstacles that hinder students from producing well-written essays is due to some limitations concerning syllabus design. Hence, textbook authors and curriculum developers can assist students by implementing Coggle mind mapping as a prewriting activity that supports creative writing.